1996
DOI: 10.1076/apab.104.2.185.12881
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Myocardial Calcium Handling in the Early Stage of Adriamycin Cardiomyopathy

Abstract: Metabolic changes have been shown to precede mechanical abnormalities in the early stages of adriamycin cardiotoxicity. This study examines the early changes in calcium homeostasis and their mechanical implications in a model of adriamycin cardiomyopathy. Hearts isolated from control and adriamycin-treated rats were coronary-perfused and isovolumic left ventricular (LV) pressure, coronary perfusion pressure and calcium transients from aequorin-loaded cardiomyocytes were recorded. Treated rats received three in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…As has been confirmed by many studies, DOX causes marked increase on cytosolic calcium level as a direct effect of disturbed calcium regulation, which in turn causes mitochondrial calcium overload (Kapelko et al, 1996;Zhou et al, 2001). In this study, it was found that MGR treatment was able to ameliorate DOX-induced increase on cytosolic calcium level.…”
Section: Discussionmentioning
confidence: 78%
“…As has been confirmed by many studies, DOX causes marked increase on cytosolic calcium level as a direct effect of disturbed calcium regulation, which in turn causes mitochondrial calcium overload (Kapelko et al, 1996;Zhou et al, 2001). In this study, it was found that MGR treatment was able to ameliorate DOX-induced increase on cytosolic calcium level.…”
Section: Discussionmentioning
confidence: 78%
“…As a result lipid-protein interactions involved in signal transduction pathways are affected [4]. Increased calcium release from sarcoplasmatic reticulum leads to cytosolic calcium overload [5]. The treatment also results in mitochondrial dysfunction with abnormal calcium-ion handling and abnormal energy metabolism [6,7].…”
Section: Mechanismmentioning
confidence: 99%
“…Myocardial damage is believed to be caused by oxidative stress induced in the myocardial cells by redox‐cycling during metabolism of the drug 2 . Different pathophysiologic mechanisms are involved that lead to reduced energy production, abnormal calcium handling, dysfunctional protein synthesis, reduced myofibrillar function, and apoptosis 3–5 . Eventually this causes increasing myocardial wall stress, remodeling, and deteriorating myocardial function as in other types of cardiomyopathy.…”
mentioning
confidence: 99%